Embroidering Identity: Women and Bugis Silk Weaving from an Ethnographic Perspective - Feby Triadi (JURNAP: Jurnal Administrasi Publik, 2025)
Bugis silk weaving is a rich cultural heritage, where women play a key role in the production process. This research uses a qualitative ethnographic approach to explore how women craftsmen embroider cultural identity through weaving practices, traditional motifs, and technical innovation. Data was collected through participant observation, in-depth interviews, and visual documentation, then analyzed thematically to reveal the relationship between technical skills, motif creativity, and the symbolic value attached to silk fabric. The research results show that women craftsmen not only maintain traditional techniques, but also adapt motifs and production processes to modern market demands, so that silk weaving functions as a medium for cultural expression, women's empowerment, and community identity. This study confirms the importance of preserving traditional practices through sustainable approaches, as well as providing an empirical contribution to the understanding of the role of women in the preservation of textile heritage and innovation in material culture.